Mediators of cerebral edema - Schilling, Lothar; Wahl, Michael (Hypoxia, 1999)
The blood-brain barrier (BBB) which is located in the continuous endothelial lining of cerebral blood vessels rigidly controls exchange of water soluble compounds under physiological conditions. Under pathological conditions such as trauma or ischemia, BBB permeability may increase thus allowing plasma constituents to escape into brain tissue. This “opening” of the BBB may, at least in part, be mediated by massive release of autacoids resulting in vasogenic brain edema. Five criteria have to be fulfilled by an individual autacoid to be considered a mediator candidate of cerebral edema: i) a permeability-enhancing action under physiological conditions, ii) a vasodilatory action, iii) the ability to induce vasogenic brain edema, iv) an increase of concentration in the tissue or interstitial fluid under pathological conditions, and v) a decrease of brain edema by specific interference with the release or action of a given autacoid. Among the mediator candidates considered, bradykinin is the only one to meet all criteria. Histamine, arachidonic acid and free radicals including nitric oxide may also be considered mediators of brain edema, but for each of these compounds evidence is less clear than for bradykinin. Although the concept of mediators inducing brain edema is well established by experimental studies, only a bradykinin receptor antagonist has so far gained entrance into clinical evaluation.